Association of 5-HT2C (Rs3813929) and UCP3 (rs1800849) gene polymorphisms with type 2 diabetes in obese women candidates for bariatric surgery - Schnor, Noa Pereira Prada [UNESP]; Verlengia, Rozangela; Novais, Patrícia Fátima Sousa [UNESP]; Crisp, Alex Harley [UNESP]; de Souza Leite, Celso Vieira [UNESP]; Rasera-Júnior, Irineu; de Oliveira, Maria Rita Marques [UNESP] (My University, 2017)
Objective: Obesity can cause systemic arterial hypertension (SAH) and type 2 diabetes mellitus (DM2) factor that is also influenced by genetic variability. The present study aims to investigate the association between gene polymorphisms related with obesity on the prevalence of SAH and DM2 in the preoperative period and 1 year after Roux-en-Y gastric bypass surgery. Subjects and methods: In total, 351 obese women in a Brazilian cohort completed the study. The clinical diagnosis of SAH and DM2 was monitored from medical records. Twelve gene polymorphisms (rs26802; rs572169; rs7799039; rs1137101; rs3813929; rs659366; rs660339; rs1800849; rs7498665; rs35874116; rs9701796; and rs9939609) were determined using real-time polymerase chain reaction and TaqMan assay. Results: In the preoperative period, prevalence of SAH and DM2 was 57% and 22%, respectively. One year postoperatively, 86.8% subjects had remission of DM2 and 99.5% had control of SAH. Subjects with T allele from the serotonin receptor gene (5-HT2C, rs3813929) had five times greater chance of DM2, and the CC genotype from uncoupling protein 3 gene (UCP3, rs1800849) had three times greater chance in the preoperative period. Conclusion: These findings indicate that polymorphisms rs3813929 and rs1800849 from 5-HT2C and UCP3 genes were related to DM2 prevalence among the Brazilian obese women candidates for bariatric surgery.
Keywords: Gene polymorphism; Hypertension; Obesity; Type 2 diabetes